Investigation of Surface Roughness and MRR for Engineering Polymers with the Abrasive Water Jet Turning Process - Kartal, F.; Yerlikaya, Z. (Walter de Gruyter GmbH, 2016)
Abstract This study investigates the abrasive water jet turning (AWJT) process of commonly used plastics, such as polytetrafluoroethylene (PTFE), castamide, and polyamide (PA), in engineering. Machining parameters were used as follows: nozzle feed rate (10, 30, and 50 mm min−1), abrasive flow rate (50, 250, and 450 g min−1), and spindle speed (1 000, 2 000, and 3 000 min−1). The effects of the machining parameters on the average surface roughness and material removal rate were investigated. According to results, average surface roughness and material removal rate were affected by the nozzle feed rate by 87.15 % and 82.48 %, abrasive flow rate by 9.84 % and 13.49 %, and spindle speed by 1.09 % and 0.08 %, respectively. Optimization results that the nozzle feed rate should be 10 mm min−1, while the abrasive flow rate is 450 g/min and spindle speed is 3 000 min−1 in order to obtain the minimum surface roughness and maximum material removal rate.
Keywords: 13. Climate action